The genetic basis for individual differences in mRNA splicing and APOBEC1 editing activity in murine macrophages - Hassan, Musa A.; Butty, Vincent; Jensen, Kirk D.C.; Saeij, Jeroen P.J. (Genome Research, 2014)
Alternative splicing and mRNA editing are known to contribute to transcriptome diversity. Although alternative splicing is pervasive and contributes to a variety of pathologies, including cancer, the genetic context for individual differences in isoform usage is still evolving. Similarly, although mRNA editing is ubiquitous and associated with important biological processes such as intracellular viral replication and cancer development, individual variations in mRNA editing and the genetic transmissibility of mRNA editing are equivocal. Here, we have used linkage analysis to show that both mRNA editing and alternative splicing are regulated by the macrophage genetic background and environmental cues. We show that distinct loci, potentially harboring variable splice factors, regulate the splicing of multiple transcripts. Additionally, we show that individual genetic variability at the Apobec1 locus results in differential rates of C-to-U(T) editing in murine macrophages; with mouse strains expressing mostly a truncated alternative transcript isoform of Apobec1 exhibiting lower rates of editing. As a proof of concept, we have used linkage analysis to identify 36 high-confidence novel edited sites. These results provide a novel and complementary method that can be used to identify C-to-U editing sites in individuals segregating at specific loci and show that, beyond DNA sequence and structural changes, differential isoform usage and mRNA editing can contribute to intra-species genomic and phenotypic diversity.